A Systematic Review of Key Factors in the Effectiveness of Multisector Alliances in the Public Health Domain. Issue 1 (January 2021) - Wiggins, Bonnie; Anastasiou, Kim; Cox, David N.
Objective: The purpose of this systematic literature review is to assess the factors associated with synergistic multisector alliances in the public health domain. Data Source: Articles in PubMed, CINAHL, Scopus, and Google Scholar between March 2009 and February 2019 were searched. Study Inclusion and Exclusion Criteria: Included alliances had a public health and behavioral focus, were from the public or private sector, and were multipartner and multisector, and from high-income countries. Public health research alliances were included, but clinical research alliances were excluded. Data Extraction: Data extraction included alliance description, alliance domain, country, single or multiple alliances, and the sectors included in the alliance. Two theoretical frameworks were used in data extraction. Data Synthesis: Data were coded according to 28 factors representing antecedents, management, and evaluation (Parent and Harvey model) and 3 output-specific factors (Bergen model). Results: A final 24 papers were included, of which 58% contained synergistic alliances. While almost all factors reportedly enabled synergy, some factors were more frequently associated with synergistic alliances, including clear purpose and positive coordination, information sharing, and evaluation of project outcomes. Complexity within some factors was also reported. Conclusion: The theoretical models were supported by the data. Public health alliances would likely benefit from incorporating factors identified as beneficial for synergy and from carefully considering the management of complex factors.